How do firms develop Innovation capabilities: a cross-national study using the coevolution theory - Rebelo, Rômulo Marcos Lardosa (2023)
There is limited discussion on how the development of Innovation capabilitiy takes place considering the simultaneous evolution between companies and their Institutional environment. Additionally, most studies about Innovation capability development present a cross-sectional research design, leading primarily to a “static” perspective, with limited discussion on their development and evolution over time. This study aims to explore how the development process of innovation capability occurs using a historical perspective and through the lens of coevolution theory, allowing the identification of the historical pattern of organization adaptations that emerge gradually over time and recognizing how organizations and environments coevolve from a multilevel perspective. A comparative analysis between two countries, Brazil and France, was carried out to capture differences in national environments. In particular, the focus was on the Electricity utility Industry firms, which have been challenged to re-evaluate their business models due to the impacts of new technologies, such as the emergence of renewable energy sources (RES). The methodological approach adopted was the multiple case study, considered appropriate to understand better how new phenomena, not yet completely known, occur and why they occur. A documental analysis was also developed to identify important events in the companies and in the regulatory environment that could affect the Innovation capability development. The results indicate that Innovation capability development is influenced by the increase in the firm’s scope of business and that there is evidence that innovation capability development converges into the same initiatives under global governance in a regulated industry. Considering the co-evolution theoretical perspective, a multilevel framework is also proposed that highlights the Institutional environmental influence on a firm’s Innovation capability and an update of the Innovation capability concept.